Using kidney size for early detection of contrast‐induced nephropathy in the emergency department setting. Issue 3 (17th May 2018) - Hongo, Takashi; Tsuchiya, Midori; Inaba, Mototaka; Takahashi, Kenji; Nozaki, Satoshi; Fujiwara, Toshifumi; Hiramatsu, Makoto
Abstract : Aim: We aimed to examine the relationship between kidney size and contrast‐induced nephropathy (CIN) in patients who underwent contrast‐enhanced computed tomography (CT) in the emergency department. Methods: This single‐center retrospective observational study was undertaken to evaluate risk factors for CIN at Okayama Saiseikai General Hospital (Okayama, Japan) from January 2014 through to December 2016. Contrast‐induced nephropathy was defined as an absolute increase in serum creatinine level of ≥0.5 mg/dL or ≥25% over the baseline value within 72 h after contrast‐enhanced CT. Independent risk factors for CIN were determined by multiple logistic regression analysis. The thickness of the kidney was evaluated as a predictor of CIN using the area under the receiver operating characteristic curve. We also analyzed CIN as an outcome using the Kaplan–Meier method. Results: The incidence of CIN was 26/262 (9.9%). In the multivariate analysis, CIN was associated with renal thickness (odds ratio = 0.65; 95% confidence interval, 0.53–0.81). No patient underwent renal replacement therapy. Conclusion: Renal thickness could be used as a reliable, simple, and easily obtainable marker for identifying CIN in patients undergoing contrast‐enhanced CT in the emergency department. Abstract : Kidney size was measured manually using the distance between computed tomography images in the slice of the renal vein. Renal thickness was easily obtained and significantly associated with contrast‐induced nephropathy.